Fish Oil Improves Pathway-Oriented Profiling of Lipid Mediators for Maintaining Metabolic Homeostasis in Adipose Tissue of Prediabetic Rats - Dasilva, Gabriel; Lois, Salomé; Méndez, Lucía; Miralles-Pérez, Bernat; Romeu, Marta; Ramos-Romero, Sara; Torres, Josep L.; Medina, Isabel (Frontiers in Immunology, 2021)
Adipose tissue is now recognized as an active organ with an important homeostatic function in glucose and lipid metabolism and the development of insulin resistance. The present research investigates the role of lipid mediators and lipid profiling for controlling inflammation and the metabolic normal function of white adipose tissue from rats suffering from diet-induced prediabetes. Additionally, the contribution to the adipose lipidome induced by the consumption of marine ω-3 PUFAs as potential regulators of inflammation is addressed. For that, the effects on the inflammatory response triggered by high-fat high-sucrose (HFHS) diets were studied in male Sprague–Dawley rats. Using SPE-LC-MS/MS-based metabolo-lipidomics, a range of eicosanoids, docosanoids and specialized pro-resolving mediators (SPMs) were measured in white adipose tissue. The inflammatory response occurring in prediabetic adipose tissue was associated with the decomposition of ARA epoxides to ARA-dihydroxides, the reduction of oxo-derivates and the formation of prostaglandins (PGs). In an attempt to control the inflammatory response initiated, LOX and non-enzymatic oxidation shifted toward the production of the less pro-inflammatory EPA and DHA metabolites rather than the high pro-inflammatory ARA hydroxides. Additionally, the change in LOX activity induced the production of intermediate hydroxides precursors of SPMs as protectins (PD), resolvins (Rv) and maresins (MaR). This compensatory mechanism to achieve the restoration of tissue homeostasis was significantly strengthened through supplementation with fish oils. Increasing proportions of ω-3 PUFAs in adipose tissue significantly stimulated the formation of DHA-epoxides by the cytochrome P450, the preference of 12LOX for DHA, so as higher production of non-enzymatic EPA-metabolites. Finally, protectin PDx was significantly reduced in the adipose tissue of prediabetic rats and highly enhanced through ω-3 PUFAs supplementation. Taken together, these actively coordinated modifications constitute key mechanisms to restore adipose tissue homeostasis with an important role of lipid mediators. This compensatory mechanism is reinforced through the supplementation of the diet with fish oils having high and balanced contents of EPA and DHA. The study highlights new insides on the targets for effective treatment of incipient diet-induced diabetes and the mechanism underlying the potential anti-inflammatory action of marine lipids.